The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2355/isijinternational.49.365
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Solidified Shell Just below the Meniscus in Continuous Casting Mold

Abstract: In the high speed continuous casting of hypo-peritectic steel slabs, growth of solidified shell just below the meniscus in the mold was researched. Rate of cooling and solidification was estimated on the basis of experimental results of thickness profiles of solidified shell, heat flux in the mold and dendrite arm spacing in the solidified structure beneath the surface of the slabs cast at 3-5 m/min.As a result, it was found that there is a delaying period of solidification growth at the beginning, till the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…In this experimental procedures, the liquid steel directly touches with the chill copper mold, therefore, it is expected that the initial heat flux should reach about 10MW/m 2 [11], which is higher than a few MW/m 2 in ordinary C.C. processes [12]. However, such a high initial heat flux immediately decreases in a second to the level of ordinary C.C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experimental procedures, the liquid steel directly touches with the chill copper mold, therefore, it is expected that the initial heat flux should reach about 10MW/m 2 [11], which is higher than a few MW/m 2 in ordinary C.C. processes [12]. However, such a high initial heat flux immediately decreases in a second to the level of ordinary C.C.…”
Section: Methodsmentioning
confidence: 99%
“…From this measurement, the minimum solidification velocity was estimated to be about 0.5mm·s -1 . As for the maximum solidification velocity near the copper mold, we refer to about 3mm·s -1 , which was estimated in continuously cast slab by the analysis of heat flow [12], because the cooling condition and the as-cast structures in our experimental equipment are quite similar to those in the continuous casting [13]. In our experiment, the initial heat flux should be higher than that in ordinary C.C.…”
Section: Numerical Analysis For the Transition Of Primary Crystalmentioning
confidence: 99%
“…From many previous investigations showed that there exists a peak (maximum) mold heat transfer rate at certain point of casting mold. For example, Hanao et al 12) reported that 45 mm below meniscus is the position of peak heat transfer rate while Meng et al 13) suggested 55 mm below the meniscus. The heat transfer in the casting mold can be regarded as 1-dimensional below the position of peak heat transfer rate, as schematically shown in Fig.…”
Section: Evaluations Of Mold Fluxes Testedmentioning
confidence: 99%
“…Contrary to the generalized perception, slag infiltration fluctuates not only in the casting direction but also along the mould width. A clear example of this behaviour is the use of inverted port SEN's to promote heat delivery to the meniscus and ensure lubrication in the mould corners 82,83) (Fig. 12).…”
Section: Effect Of Flow Dynamics Heat Transfer and Solidificationmentioning
confidence: 99%